2023
DOI: 10.1515/ijcre-2022-0191
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of trickle bed reactors for the purification of 1-butene

Abstract: In this contribution, a mathematical model of an industrial trickle-bed reactor employed in the purification of a C4 cut by selective hydrogenation of acetylenic or dienes compounds to obtain high purity 1-butene is presented. A reaction network of ten reactions is included in the model, with kinetics expressions and parameter estimation obtained from previous experimental studies on a commercial catalyst. Internal mass transfer resistances in the catalyst particles are significant; therefore the reaction-diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…33–36 The Barreto group studied the kinetics of selective hydrogenation of butyne- and butadiene–butene mixtures in trickle bed reactors. 37,38 They demonstrated that the local concentration of polyunsaturated molecules sharply dropped inside the catalyst grains due to internal mass transfer limitations. These results gave valuable insights into some parameters determining selectivity during selective hydrogenation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…33–36 The Barreto group studied the kinetics of selective hydrogenation of butyne- and butadiene–butene mixtures in trickle bed reactors. 37,38 They demonstrated that the local concentration of polyunsaturated molecules sharply dropped inside the catalyst grains due to internal mass transfer limitations. These results gave valuable insights into some parameters determining selectivity during selective hydrogenation reactions.…”
Section: Introductionmentioning
confidence: 99%